2017
DOI: 10.1002/jmv.24958
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of enterovirus A71 isolates from severe neurological cases in Poland

Abstract: The aim of this study was to report a minor outbreak of enterovirus A71 (EV-A71) infection in Poland and characterize isolates from cases of severe neurological infection detected in 2013 and 2016. Phylogenetic analysis revealed that Polish strains belonged to the C genogroup: C1, C2, and C4. Severe neurological manifestations as encephalitis or acute flaccid paralysis (AFP), were associated with all detected subgenogroups. The C2 subgenogroup was associated with the outbreak in Gdansk, with serious cases of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The outbreak caused a 35-fold increase in hospitalization rates in comparison to the previous year [ 8 ]. Acute flaccid paralysis associated with enterovirus 71 was also previously reported in Poland [ 9 ]. Recently we have shown that enteroviruses are the most frequently detected pathogens in children with infection of the CNS hospitalized in Bialystok, Poland [ 10 ].…”
Section: Introductionsupporting
confidence: 62%
“…The outbreak caused a 35-fold increase in hospitalization rates in comparison to the previous year [ 8 ]. Acute flaccid paralysis associated with enterovirus 71 was also previously reported in Poland [ 9 ]. Recently we have shown that enteroviruses are the most frequently detected pathogens in children with infection of the CNS hospitalized in Bialystok, Poland [ 10 ].…”
Section: Introductionsupporting
confidence: 62%
“…Reports of severe clinical presentation associated with detection of a EV-A71 C1-like strains [3,5-7], together with recent indications of long-term sequelae [13,14], should be a signal for physicians and public health authorities to include/intensify EV diagnostic in patients showing signs of aseptic meningitis, encephalitis or acute flaccid paralysis/myelitis.…”
Section: Discussionmentioning
confidence: 99%
“…2015 ). In particular, four cases of aseptic meningitis caused by viruses of the C2 sub-genogroup were identified in Poland in mid-late 2016 ( Wieczorek et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%